2018
DOI: 10.1155/2018/8121634
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Status, Body Composition, and Glycaemic Control in Adolescents with Type 1 Diabetes Mellitus

Abstract: Background Disturbed bone turnover, osteoporosis, and increased fracture risk are late complications of insulin-dependent diabetes mellitus. Little is known about how far and to what extent can glycaemic control of type 1 diabetes mellitus (T1DM) prevent disturbances of bone health and body composition during the growth and maturation period. Objective The aim of this cross-sectional study was to compare the skeletal status outcomes and body composition between patients stratified by glycaemic control (1-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 83 publications
5
35
0
2
Order By: Relevance
“…The indicators of fat metabolism, such as triglyceride and cholesterol levels, were higher than normal in patients with combined endocrine disorders compared to those in DM patients. Similar results were noted in other papers (21, 22). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The indicators of fat metabolism, such as triglyceride and cholesterol levels, were higher than normal in patients with combined endocrine disorders compared to those in DM patients. Similar results were noted in other papers (21, 22). …”
Section: Discussionsupporting
confidence: 93%
“…In addition, a compensatory increased PTH level was observed in patients with DM + AIT with coinciding reduced 25(OH)D concentration (less than 75.0 nmol/L). Some authors have postulated the possibility of a relationship with coexisting 25(OH)D concentrations (3, 15, 21). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potential health benefits of vitamin D sufficiency remain unknown in our population; however, the problem of vitamin D deficiency has been recently highlighted in Polish patients suffering from multiple sclerosis, 32 systemic lupus erythematosus, 33 metabolic syndrome, 34 primary hypertension, 35 or type 1 diabetes. 36 Moreover, the distribution of 25(OH)D levels related to age, sex, place of residence, and anthropometric characteristics has not yet been investigated. The aim of this cross-sectional study was to determine the current vitamin D status in a representative sample of men and women living in the urban areas of various regions of Poland, based on an assessment of the serum 25(OH)D level.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cholecalciferol supplementation is associated with an improved glycaemic control in T1D [16][17][18][19]. Conversely, VDD is associated with poor control [22]. Improvement in vitamin D status improves endogenous insulin secretion and insulin sensitivity of target tissues, thereby contributing to an improved insulin action [17][18][19].…”
Section: Discussionmentioning
confidence: 99%